(untitled) (Journal of history, 2022)
During the Soviet period, the documents of the Archival Fund of the CPSU, which directly supervised the work of state and public institutions of the country, occupied a special place in the study of the history of the country. Party documents that were not included in the state archival fund and stored in the party archives in secrecy mode 80 percent of them had secrecy stamps. The main issues of the introduction into scientific circulation of party documents that became part of the National Archival Fund after the collapse of the USSR were: their integration, systematization and declassification. The purpose of the study: to describe the process and level of declassification of CPSU documents in post-Soviet states, to reveal the principles that guided declassification. The article discusses the issues of declassification of documents of the Communist Party of Kazakhstan, stored in the Archive of the President of the Republic of Kazakhstan, which have different labels of secrecy for political and ideological reasons of Soviet totalitarianism, with the aim of widespread introduction into scientific circulation. The author notes that in Soviet period, the party apparatus strictly controlled the use of archival information and access to party documents as a tool for ideologizing society. The author analyzes the works of scientists and archivists on legal, methodical, organizational and technical issues of declassification of archival documents of the CPSU in the post-Soviet states